Women@Work (Chinese version) - CHUA, Roy (Institutional Knowledge at Singapore Management University, 2020)
This series of six short two-part cases (“caselets”) is written to highlight workplace dynamics faced by women professionals. Women represent about half of the global workforce but they face distinct workplace issues compared to men. We will examine some of these issues through these caselets, which are written from the personal perspectives of the protagonists. They are real-life stories that many should be able to relate to. Although all the protagonists are women, this does not mean that the lessons are not applicable to men. Men and women work alongside one another at the workplace and men play a critical role in shaping women’s workplace experience. Throughout the case discussions, the perspectives of men will be immensely valuable. We recognise that the instructor cannot possibly do justice to these cases in a 90-minutes class. It is also not our goal to solve the larger social and gender issues that are implicated in these cases. Our aim is primarily to help students better appreciate the challenges women face, and collectively think of ways to handle them. Although the cases have been written in the Asian context, these issues can occur anywhere. The students will be made aware of some basic frameworks and strategies that can help them think about and manage the challenges that women face at work, and draw on their experiences and insights to generate ways of handling these vexed interactions, which could also enable women to make greater progress and contributions in innovation work.